Micro Coriolis Mass Flow Sensor with Large Channel Diameter Realized by HNA Wet Etching - Qihui Yu; Maarten J. S. Bonnema; Mahdieh Yariesbouei; Remco J. Wiegerink; Joost C. Lötters (Sensors)
This paper introduces a Coriolis mass flow and density sensor. The sensor is made using Surface Channel Technology (SCT) but with selective wet etching to create the channels. This method forms suspended microfluidic channels with a larger cross-sectional area. Because of this larger cross-sectional area, the sensor has a much higher flow range, up to 50 <semantics>g h−1</semantics> (for water) with a pressure drop of 1 bar, compared to the standard SCT-based Coriolis sensor, which is only 1.2 <semantics>g h−1</semantics>. The channel has a semi-elliptical cross-sectional area, measuring 200 micrometers wide and 70 micrometers deep. The channel wall is made of a stack of thin films with a total thickness of 2.5 <semantics>μm</semantics>. Water, isopropyl alcohol (IPA), and nitrogen (N2) are used to test and evaluate the sensor’s mass flow and density sensing performance.